Integrating Neuroembryology into Islamic Education: A Brain Development-Based Neuro-Pedagogical Framework - Bukhari Bukhari; Muksinin Muksinin; Almawadi Almawadi; Deby Habja Musdalifa; Ahmad Lahmi; Julhadi Julhadi (Ruhama : Islamic Education Journal, 2026)
The development of neuroscience has significantly influenced contemporary educational studies, particularly in understanding brain development and learning processes. However, studies integrating neuroembryology and Islamic education remain limited, especially in constructing a neuro-pedagogical framework based on brain development. This study aims to analyze the integration of neuroembryology and Islamic education in developing a brain development-based neuro-pedagogical framework. This research employed a qualitative approach using a Systematic Literature Review (SLR) method guided by the PRISMA framework. Data were collected from scientific articles indexed in Scopus, ScienceDirect, SpringerLink, DOAJ, and Google Scholar published between 2019 and 2025. A total of 42 relevant articles were analyzed using content analysis and thematic synthesis techniques. The findings reveal that neuroembryology has a significant relationship with learning readiness, emotional regulation, cognitive development, and character formation. The study also found that the principles of brain-based learning are substantially aligned with Islamic educational values such as fitrah, tarbiyah, ta’dib, tazkiyah, and akhlaq development. Based on the synthesis results, this study proposes a conceptual framework of Islamic neuro-pedagogy integrating neuroembryology, brain-based learning, and Islamic educational values into a holistic learning model. This research contributes theoretically to the integration of neuroscience and Islamic education and practically to the development of curriculum design, learning strategies, and neuroscience-based Islamic educational practices.Keyword: Neuroembryology, Islamic education, neuroscience, brain-based learning, neuro-pedagogy.